Developing listening materials for the second-grade multimedia department students of SMKN 2 Wonosari based on 2013 curriculum - Galuh Sekar Widiyati (Journal of English Language and Pedagogy, 2020)
The aims of this study were (1) to develop listening materials for the second-grade students of Multimedia Department of SMKN 2 Wonosari Gunungkidul and (2) to describe the effectiveness of the listening materials for the second-grade students of Multimedia students of SMKN 2 Wonosari Gunungkidul. The study applied Educational Research and Development (R&D) using simplified three steps Borg and Gall. The steps were (1) research and information collecting that was conducted by performing document analysis, class observation, and interview, (2) product and development which included drafting, internal expert judgment and revision (3) field testing which conducts tryout, external expert judgment and revision. The findings showed that (1) the listening material using Borg and Gall's model considered as effective teaching material for the second-grade students of Multimedia Department of SMKN 2 Wonosari Gunungkidul (2) the effectiveness of the listening material helped the students in improving their listening skill.Â Â